Photodynamic therapy as an up-to-date medical technology for the treatment of vulgar acne - D. A. Andreev; A. A. Zavyalov; T. N. Ermolaeva; A. G. Fisun; K. I. Polyakova; V. A. Dubovtseva; T. E. Maksimova (State Scientific Center of Dermatovenereology and Cosmetology, 2020)
Background. Acne occurs in at least 85 % of male and female teenagers, often lasts a long time, with relapses in the 3rd and 4th decades of life. Since 2000, the technology of photodynamic therapy (PDT) has been actively used in many countries. Over the past two years, numerous important studies on the effectiveness of PDT for the treatment of acne have been conducted.Aim. To generalize most recent information on the effects of PDT and to show its applicability in clinicalpractice.Methods. The data search and analysis were carried out using the US National Library of Medicine (PubMed database) and E-library online resources. The study included original articles published over the past two years and devoted to or related to the use of PDT for the treatment of acne vulgaris.Results. A total of 55 articles were discovered. A total of 9 clinical trials or descriptions of clinical cases meeting the criteria for analysis were selected. The investigated clinical studies used various and ambiguous, non-standardized approaches in terms of photosensitizer incubation periods, cumulative doses of the light source energy and the number of treatment sessions. An analysis of the publications revealed a trend to use shorter incubation periods and less active photosensitizers in order to reduce the risk of such adverse events as erythema, edema, hyperpigmentation and blistering.Discussion and conclusions. PDT is an effective and promising medical technology for the treatment of acne. PDT can be used for mild and severe inflammatory and cystic acne in patients with various skin types and lesion localizations. This type of acne therapy is currently performed using various approaches. Further research is needed to develop optimal and standard procedures for implementing this relevant and clinically beneficial medical technology.